Antioxidant and Antidiabetic Properties of a Thinned-Nectarine-Based Nanoformulation in a Pancreatic β-Cell Line - Elisabetta Schiano; Ettore Novellino; Marta María Gámez Fernández; Helena Tiekou Lorinczova; Gian Carlo Tenore; Fortuna Iannuzzo; Vinood B. Patel; Satyanarayana Somavarapu; Mohammed Gulrez Zariwala (MDPI AG, 2023)
Pancreatic β-cells play a crucial role in maintaining glucose homeostasis, although they are susceptible to oxidative damage, which can ultimately impair their functionality. Thinned nectarines (TNs) have gained increasing interest due to their high polyphenol and abscisic acid (ABA) content, both of which possess antidiabetic properties. Nevertheless, the efficacy of these bioactive compounds may be compromised by limited stability and bioavailability in vivo. This study aimed to develop nanoformulations (NFs) containing pure ABA or a TN extract (TNE) at an equivalent ABA concentration. Subsequently, the insulinotropic and antioxidant potential of the NFs and their unformulated (free) forms were compared in MIN-6 pancreatic cells exposed to varying glucose (5.5 mM and 20 mM) and iron (100 µM) concentrations. NF-TNE treatment exhibited enhanced antioxidant activity compared to free TNE, while ABA-based groups showed no significant antioxidant activity. Moreover, MIN6 cells incubated with both high glucose and iron levels demonstrated significantly higher insulin AUC levels after treatment with all samples, with NF-TNE displaying the most pronounced effect. In conclusion, these results highlight the additional beneficial potential of TNE due to the synergistic combination of bioactive compounds and demonstrate the significant advantage of using a nanoformulation approach to further increase the benefits of this and similar phytobioactive molecules.